Housing market bubbles and business cycles in an agent-based credit economy - Einar Jon Erlingsson; Silvano Cincotti; Hlynur Stefansson; Jon Thor Sturlusson; Andrea Teglio; Marco Raberto (Kiel Institute for the World Economy (IfW), 2013)
In this paper the authors present an agent-based model of a credit network economy. The artificial economy includes different economic agents that interact using simple behavioral rules through various markets, i.e., the consumption goods market, the labor market, the credit market and the housing market. A set of computational experiments, based on numerical simulations of the model, have been carried out in order to explore the effects of different households' creditworthiness conditions required by the banking system to grant a mortgage. The authors find that easier access to credit inflates housing prices, triggering a short run output expansion, mainly due to the wealth effect. Also, with a more permissive policy towards household mortgages, and thus higher levels of credit, the artificial economy becomes more unstable and prone to recessions usually caused by falling housing prices. Often the authors find that an initial crisis can leave firms in a fragile state. If the situation is not cured, a subsequent crisis can lead to mass bankruptcies of firms with catastrophic effects on the credit sector and on the real economy. With stricter conditions on household mortgages the economy is more stable and does not fall into serious recessions, although a too severe regulation can slow down economic growth.
Keywords: E20; E25; G21; R31; R38; 330; Credit cycles; housing market; agent-based model; subprime lending